Second chance summer ebook - Hannon, Irene (2014)
Restoring Hearts When Rachel Shaw and Jack Fletcher meet on a sunny Georgia beach, it seems like the perfect start to a romance. There's just one problem--neither one is the least bit interested in falling in love. They're just looking for peace, and time to work through their losses. But Rachel's aunt Eleanor and Fletch's Gram have other plans. Their meddling matchmaking would drive Rachel and Fletch nuts if they weren't busy restoring a house for one of Gram's charities. Yet as they repair the house, it's their hearts that begin to mend. Soon Rachel and Fletch realize they might be able to build a second chance at a great love.